Impact of Resilience and Coping Strategy on Post-Traumatic Symptoms Among Muslim University Students - Kusmawati Hatta; Abizal Muhammad Yati; Azhari Azhari; Muslima Muslima; Syaiful Indra (Islamic Guidance and Counseling Journal, 2023)
This study examined the association between resilience and coping strategies on post-traumatic stress symptoms in Muslim university students. The study used a cross-sectional design and gathered data from 1157 participants using four questionnaires. The results showed that higher levels of resilience were related to higher coping strategies and lessened post-traumatic stress symptoms. In comparison, higher levels of coping strategies were correlated with lower levels of post-traumatic stress symptoms. In addition, the regression analysis revealed that resilience and coping strategies were significant predictors of post-traumatic stress symptoms, with resilience predicting lower levels of post-traumatic stress symptoms and coping strategies predicting higher levels. These findings suggest that interventions focusing on improving resilience and coping strategies may help reduce post-traumatic stress symptoms among Muslim university students. However, further research is needed to confirm these findings and examine this association's underlying mechanisms.